(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2026)
Timber is naturally combustible, which makes timber structures vulnerable to fire. Hence, maintaining a balance between structural strength and fire resistance is crucial to ensure safety and durability. When exposed to high temperatures, timber undergoes thermochemical decomposition through pyrolysis, ignition, and char formation, altering its chemical composition and physical structure. The formation of a charred outer layer serves as an insulator, reducing heat penetration and protecting the core. This process makes the charring rate a critical parameter in fire-resistant design, influencing the structural performance and safety of timber under fire exposure. Therefore, this study examines the relationship between char depth and charring rate in five Malaysian tropical hardwood species (Keranji, Resak, White Meranti, Kedondong, and Jelutong), with densities ranging from 450 kg/m³ to over 1000 kg/m³. The timber samples were tested under standard fire exposure ISO 834 (equivalent to BS 476: Part 20), using a large furnace under one-dimensional charring conditions for a duration of 60 minutes, during which internal temperatures were continuously recorded via embedded thermocouples. The experimental data revealed significant interspecies variation in charring rates, with denser species such as Keranji exhibiting slower char development than lower-density specimens like Jelutong. Charring rates were benchmarked against the Eurocode 5 (EC5)–recommended value of 0.5 mm/min, with most tested species performing favorably under the specified conditions. One-way ANOVA indicated statistically significant differences between species (p < 0.05), supported by coefficient of variations (COV) values that demonstrated the reliability and repeatability of the observed trends. These findings contribute to critical baseline data for structural fire design in tropical regions, thereby improving the accuracy of charring rate estimation for local timber species. The results support the development of more tailored, performance-based fire safety strategies aligned with international standards.